Anthrozoology Research on the Relationship between Elephants and Buddhist- Jataka Stories. - Muthukumarana, Tharindu (Journal of International Buddhist Studies, 2021)
During the early Vedic-Period elephants were not much embraced as a symbol of royalty and records were scarce. By the time of the Late-Vedic period, elephants were trending on royal usage. As Gautama Buddha’s existence range from 560 BC-480BC, the Buddhism related elephants records can be one of the oldest archives on captive elephants. From 547 Jataka stories about 126 stories were detected to have some sort of relationship with elephants. What is presented in this paper is just glimpse of a review on such Jataka stories. This work had been compared with other historical records for better understanding.